IBN ARABI’S HERMENEUTICS AS AN ALTERNATIVE RELIGIOUS EXEGESIS FOR CONTEMPORARY URBAN MUSLIM COMMUNITIES - Hidayatulloh, Taufik; Saumantri, Theguh; Hajam, Hajam; Akmaliah, Wahyudi (AKADEMIKA: Jurnal Pemikiran Islam, 2025)
The understanding of religious texts in contemporary Muslim communities is often dominated by a rigid literal approach that overlooks the inner dimensions and social contexts. In facing the challenges of modernity, pluralism, and the complexities of urban life, an alternative interpretation that is more inclusive and flexible is needed. Ibn Arabi, a Sufi and Islamic philosopher, offers profound hermeneutics through the power of imagination, symbolism, ‘irfani epistemology, and his mystical system of knowledge. This study aims to explore Ibn Arabi’s hermeneutical concepts as an alternative religious interpretation relevant to contemporary urban Muslim communities. The method employed is a literature review using a hermeneutical approach, involving an in-depth analysis of Ibn Arabi’s major works, such as al-Futuhat al-Makiyyah and Fusus al-Hikam, along with modern interpretations of his intellectual legacy. The findings reveal that Ibn Arabi’s hermeneutics provide a strong foundation for understanding religious texts more holistically, integrating the inner and outer dimensions through methods such as ta’wil, kashf, and mushahadah. Ibn Arabi’s approach is relevant for urban communities as it bridges tradition and modernity, fostering a spiritual, inclusive, and contextual understanding of religion. His intellectual legacy not only addresses the challenges of modern religious interpretation but also opens up spaces for dialogue between Islamic traditions and contemporary societal needs.